Glutathione-Loaded Solid Lipid Microparticles as Innovative Delivery System for Oral Antioxidant Therapy - Serena Bertoni; Beatrice Albertini; Carlotta Facchini; Cecilia Prata; Nadia Passerini (MDPI AG, 2019)
The present study aimed to develop a novel formulation containing glutathione (GSH) as an oral antioxidant therapy for the treatment of oxidative stress-related intestinal diseases. To this purpose, solid lipid microparticles (SLMs) with Dynasan 114 and a mixture of Dynasan 114 and Dynasan 118 were produced by spray congealing technology. The obtained SLMs had main particle sizes ranging from 250 to 355 µm, suitable for oral administration. GSH was efficiently loaded into the SLMs at 5% or 20% w/w and the encapsulation process did not modify its chemico-physical properties, as demonstrated by FT-IR, DSC and HSM analysis. Moreover, in vitro release studies using biorelevant media showed that Dynasan 114-based SLMs could efficiently release GSH in various intestinal fluids, while 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay demonstrated the good radical scavenging activity of this formulation. Dynasan 114-based SLMs exhibited an excellent biocompatibility on intestinal HT-29 cells at concentrations up to 2000 μg/mL. SLMs containing GSH alone or together with another antioxidant agent (catalase) were effective in reducing intracellular reactive oxygen species (ROS) levels. Overall, this study indicated that spray congealed SLMs are a promising oral drug delivery system for the encapsulation of one or more biological antioxidant agents for local intestinal treatment.